Analysis of cardiopulmonary bypass status in China: eight-year development trends. (January 2013) - Zhao, M; Wu, B; Yang, S; Long, C
Objective: To study the development of cardiopulmonary bypass (CPB) in the past 8 years and to come up with predictions and recommendations for the future in China. Methods: Domestic hospitals performing cardiovascular operations were supplied with questionnaires, annually (between 2003 and 2008), upon the number of on-pump and off-pump cardiovascular operations, oxygenators of different types and the number of extracorporeal membrane oxygenation (ECMO). All the hospitals in this study were divided into 8 grades, according to the number of cardiovascular operations. The market share of hospitals in each grade was analyzed. Results: The total anumber of cardiovascular operations was 170, 547 in 2010, of which 136, 753 were performed under CPB. The ratio of imported membrane oxygenators increased from 43.22% in 2003 to 59.75% in 2010, while bubble oxygenator composition decreased from 43.78% in 2003 to 14.59% in 2010. Forty-four hospitals carried out 206 cases of ECMO in 2010. There were 32 hospitals that performed cardiovascular operations of over 1, 000 cases and their market share was 43%. There were 255 hospitals that performed cardiovascular operations in less than 50 cases and their market share was only 3%. Conclusions: CPB in China has gone through a rapid development in the past eight years. Medical resources for CPB should be concentrated and systematic training regulations should be established in the future.